Are Organizational Commitment and Compensation Predicting Employee’s Performance? - Fatwa Tentama (Universitas Ahmad Dahlan, 2015)
AbstractThe problem, which an organization often faces, is the employees’ performance, which results in ineffective organization. Commitment and compensation are factors affecting the employees’ performance. This research aims at empirically examining the role of commitment and compensation of employees’ performance. The subjects of the research are permanent employees at Ahmad Dahlan University, having served for more than one year. The sampling technique is non-randomized. The method of collecting data uses commitment,compensation, and performance scales. The data are analyzed with multiple linear regression technique. The result shows that the organizational commitment and the compensation simultaneously predict the employees’ performance of (r)= 0,594 and the significance correlation coefficient of F reg. = 12.815 with p = 0,000 (p<0,01), which means there is a very significant positive correlation among organizational commitment and compensationsimultaneously with the performance of the employees of Ahmad Dahlan University. The implication of study is discussed further in article.Keywords: organizational commitment, compensation, performance